TECHNOLOGY AND INTELLECTUAL DISABILITY: PEDAGOGICAL PRACTICES FOR DIGITAL INCLUSION - Carneiro, Relma Urel Carbone; Costa, Maria Carolina Branco (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
The educational service for students with intellectual disability is a recurrent theme in the discussions of this field, in the sense of overcoming an excluding vision that considers the disability and ignores the capabilities, and searching to offer real conditions of access to knowledge coming from specificities. The use of technology has been pointed out as a pedagogical resource that can contribute in this process, making the student the protagonist, allowing the development of a number of areas of knowledge. Thus we have developed a study from an extension project linked to Unesp Teaching Center (Núcleo de Ensino da Unesp), aiming to propose and evaluate pedagogical actions through the use of computing for students with intellectual disability. The study was performed at a Special Education Center with a group of 18 students with ages between 9 and 60 years. It was based on the theoretical references of historical-critical pedagogy and historical-cultural psychology. It also used a qualitative approach and had research-action as its methodological procedure. The results obtained from evaluations, regular teachers’ reports and procedural follow-up of the participants demonstrated that the students involved were placed in digital information environments and the computer has acted as an effective pedagogical tool in the process of teaching and learning.